Aesthetic and pedagogical proposals of El Sistema: A case study of SOJ (Orfeu, 2020)
The National System of Youth and Children’s Orchestras and Choirs of Venezuela has become the most reproduced worldwide orchestral program aimed at children and youth. An approach to this was made through the System of Youth and Children’s Orchestras of Jujuy (SOJ), one of the orchestral projects distributed worldwide that corresponds to the first one. Through a case study, an analysis is made of the official discourse of both orchestral projects and of the SOJ practices observed, reflecting on the content of the objectives and the alleged breaks that the Systems propose in the pedagogical field. However, the proposals in the aesthetic field are not compatible with the attempted pedagogical breaks. The analysis shows the close relationship of pedagogy with the aesthetic aspects of the Systems. Finally, it is concluded that the alleged pedagogical breaks are closer to rhetoric and are not consonant with practices. Furthermore, the globalization of El Sistema and its meanings is interpreted more broadly in the historical construction of the symphony orchestra and musical education.
Keywords: Symphony Orchestra; El Sistema; repertoire; musical pedagogy